Problematika Izin Komisi Pemberantasan Korupsi Terhadap Upaya Penyadapan Tersangka Korupsi - Rachman , Andi Nur; Syarif, Mujar Ibnu (Legal Community Associations, 2024)
The process of revising the KPK law gave rise to a new structure within the corruption erradiction commision. With the existence of the KPK Supervisory Board, the KPK's performance must be adapted to the results of the revision of the law. This article aims to explain cases of licensing issues experienced by KPK employees or investigators in an effort to wiretap corruption suspects to the KPK Supervisory Board. This arose due to the revision of the latest KPK law, namely Law number. 19 of 2019 so that there are many bureaucracies that hinder the performance of investigators in carry out efforts to eradicate corruption. The performance of investigators who are required to be fast and immediately confronted with layers of bureaucracy related to wiretapping. The research method used is a normative juridical approach using the statutory approach. The results of the research obtained are that the latest revision of the KPK law makes the wiretapping mechanism for corruption suspects must take permits and layers of bureaucracy. After a judicial review related to Law Number 19 of 2019, the Constitutional Court granted a material claim related to the article governing wiretapping. Now the KPK only notifies the Supervisory Board no later than 14 (fourteen) work days after the wiretapping is carried out. This is a good thing because the investigator's actions are impermeable and immediately can run well.